Toll like Receptor 3 & 4 Responses of Human Turbinate Derived Mesenchymal Stem Cells: Stimulation by Double Stranded RNA and Lipopolysaccharide - Hwang, Se Hwan; Cho, Hye Kyung; Park, Sang Hi; Lee, WeonSun; Lee, Hee Jin; Lee, Dong Chang; Oh, Jeong Hoon; Park, Sun Hwa; Kim, Tai-Gyu; Sohn, Hyun-Jung; Kang, Jun Myung; Kim, Sung Won (PloS one, 2014)
Multipotent mesenchymal stromal cells (MSCs) represent a promising cell-based therapy for a number of inflammatory or autoimmune diseases. Herein, Toll like receptor (TLR) expression by MSCs and their immune regulatory roles are investigated. In this study, we investigated the influence of TLR on the immune response, proliferation, and differentiation potential of human turbinated MSC (hTMSC) cultures in vitro. After isolating hTMSCs from discarded inferior turbinate tissue, FACS analysis was used to assess the expression of TLRs such as TLR2, TLR3, TLR4, and TLR5 in hTMSCs and cell proliferation was assessed using a cell counting kit (CCK)-8. Cytokine and chemokine secretions were analyzed with multiplex immunoassays for IL-1α, IL-1β, IL-4, IL-6, IL-8, IL-10, IL-12, IP-10 (CXCL10), RANTES (CCL5), TNF-a, GM-CSF, and IFN-γ. The differentiation potential of hTMSCs was evaluated in the osteogenic, chondogenic, and adipogeinc media and analyzed by histology and gene expression related to differentiation. FACS analysis revealed that TLR3 and TLR4 expression consisted of a relatively high percentage of the surface proteins expressed by hTMSCs. The proliferation of hTMSCs was influenced and significantly increased by the presence of TLR4 agonists. In particular, hTMSCs produced a set of cytokines and chemokines and the expression of IL-6, IL-8, IL-12, IP-10 (CXCL10), RANTES (CCL5), TNF-α, and GM-CSF were up-regulated in response to the TLR4 agonist LPS. The osteogenic and adipogeinc differentiation potential of hTMSCs was not affected by TLR agonists. We conclude that TLR4 stimulation affects TLR expression, proliferation, and the immunomodulation potential of hTMSCs. Understanding the mechanism behind TLR's influence on hTMSCs and their immunomodulating properties would be useful for providing a novel target to exploit in the improvement of stem cell-based therapeutic strategies.